Cinematic Vitalism : Film Theory and the Question of Life - Pollmann, Inga (Book collections on Project MUSE., 2018)
This book draws new connections between twentieth-century German and French film theory and practice and vitalist conceptions of life from biology and philosophy. Inga Pollmann shows how the links between the two created a modernist, experimental, and cinematic strand of vitalism in and around the movie theatre. Articulated by film theorists, filmmakers, biologists and philosophers, this cinematic vitalism maps out connections among human beings, milieus, and technologies that continue to structure our understanding of film.